Le Centre d'investigation sur la rouille du caféier (CIFC) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Le Centre d'investigation sur la rouille du caféier (CIFC)A Ceylan,